(untitled) (Revista de Ciências Agroveterinárias, 2020)
Septoria leaf spot is one of the main diseases affecting tomato. Its damages vary according to susceptible cultivar, pathogen physiological races, and environmental conditions. The objectives of this study were to assess the inhibitory concentration of 50% of spores (IC50), the sensitivity reduction factor (SRF) of Septoria lycopersici isolates, and the effectiveness of fungicides traditionally used to control Septoria Leaf Spot (SLS) in tomato in the state of Santa Catarina, Brazil, during the 2016 and 2017 crop seasons. For the in vitro experiment, 13 S. lycopersici isolates were obtained from leaves displaying SLS symptoms from different tomato cultivars. The fungicides thiophanate methyl and mancozeb were evaluated at concentrations of 0.1; 1.0; 10; 100 and 1000 mg L-1 of active ingredient to determine the effective dose for inhibiting 50% of spore germination (DE50) and the sensitivity reduction factor (FRS). The S. lycopersici isolates derived from tomato crops that were sprayed with these fungicides were compared with the isolates 475-1, 475-3, 475-4, and 475-7 obtained from tomato crops that remained unsprayed. For the in vivo experiments, the preventive fungicides azoxystrobin, chlorothalonil, captan, and mancozeb and the curative fungicides thiophanate methyl, mancozeb, difenoconazole, and methconazole were sprayed at the commercial dose at 12, 24, 36, 48, 72, and 96 h before (preventive) and after (curative) the inoculation with the 475-1 S. lycopersici isolate, to evaluate the efficiency of the SLS control in tomato plants. The active ingredient thiophanate methyl and mancozeb were considered non-toxic to all S. lycopersici isolates regardless of the doses tested. The DE50 values of thiophanate methyl and mancozeb rangesd from 75 to 580 mg L-1. The preventive fungicides chlorothalonil and azoxystrobin and curative fungicides difenoconazole and metconazole were significantly efficient to control SLS in vivo.